Neutrophilic eccrine hidradenitis in two patients treated with BRAF inhibitors: a new cutaneous adverse event. (1st June 2017) - Herms, F.; Franck, N.; Kramkimel, N.; Fichel, F.; Delaval, L.; Laurent‐Roussel, S.; Carlotti, A.; Avril, M.‐F.
Summary: Neutrophilic eccrine hidradenitis (NEH) is a rare neutrophilic dermatosis, first described in patients undergoing chemotherapy for a malignant haemopathy. It has polymorphous clinical features and the association of both clinical and histological features is necessary to make a diagnosis. We report the first two cases of NEH in patients treated with a BRAF inhibitor (BRAFi), either dabrafenib or vemurafenib, for a stage IV metastatic melanoma. Disseminated erythematous plaques associated with fever and polyarthralgia occurred early after the initiation of treatment and were badly tolerated. Histological analyses confirmed the diagnosis of NEH. Symptoms disappeared a few days after the cessation of treatment and introduction of topical steroids. The replacement of one BRAFi with another is a therapeutic alternative as it is not necessarily associated with a relapse of NEH. NEH can be added to the spectrum of neutrophilic dermatoses induced by BRAFis. It occurs earlier (3–4 days) than previously described drug‐induced NEH (9–12 days) and may be an earlier stage of eccrine squamous syringometaplasia, which has already been reported in the context of BRAFi‐treated patients.